Belief, Sincerity, and Certainty in Kant’s “Theodicy” Essay - Chignell, Andrew (Con-Textos Kantianos. International Journal of Philosophy, 2026)
In this brief paper I offer an interpretation of what “sincerity” and “certainty” mean in the context of Kant’s discussion of the story of Job in the “Theodicy” essay.  I argue that, for Kant, the encounter with evil ideally leads various commitments to become reflective.